Development of an adipocyte differentiation protocol using 3T3-L1 cells for the investigation of the browning process: identification of the PPAR-γ agonist rosiglitazone as a browning reference drug - Flori, Lorenzo; Galgani, Giulia; Bray, Giorgia; Ippolito, Chiara; Segnani, Cristina; Pellegrini, Carolina; Citi, Valentina; Bernardini, Nunzia; Martelli, Alma; Calderone, Vincenzo (Frontiers in Pharmacology, 2025)
BackgroundObesity is a metabolic disease that is characterized by an excessive accumulation of adipose tissue (AT) and is often associated with other pathologies. AT is a lipid storage organ with endocrine functions that presents two main phenotypes: white adipose tissue (WAT) and brown adipose tissue (BAT). Preadipocytes or mature white adipocyte cells can differentiate in a middle phenotype with morpho/functional characteristics between WAT and BAT, known as brown-like or beige adipose tissue (BeAT), through the browning process. Considering the interest in stimulating the browning process in metabolic disorders and the lack of clarity, evenness, and reproducibility of the preclinical models, the detailed description of an adipocyte differentiation protocol and the “de novo” development of a beige adipocyte phenotype has been described. Furthermore, the most described stimuli in inducing the browning process, such as PPAR-γ agonists (using rosiglitazone, RGZ) and β-adrenergic stimulators (using isoproterenol, ISO), were evaluated in order to describe their involvement in the browning process and identify a reference compound for the induction of the “de novo” browning.MethodsImmortalized murine embryonic fibroblasts (3T3-L1) cells were differentiated for up to 17 days using a differentiation medium (DM) and a maintenance medium (MM) with or without RGZ or ISO to obtain both the mature white and the beige adipocyte phenotype. The differentiation was evaluated by the Oil Red O (ORO) staining assay, citrate synthase activity, and mitochondrial uncoupling protein 1 (UCP-1) immunodetection and expression performed on different days (T0, T3, T10, and T17) after the induction of differentiation.ResultsThe results indicated that RGZ induced morphology and ORO-positive lipid deposits and increased the activity of citrate synthase enzyme and UCP-1 levels overlapping with a beige adipocyte phenotype after 17 days. ISO did not display a significant effect in these experimental conditions.ConclusionOverall, this work describes in depth the different phases of the adipocyte differentiation process by offering a detailed and reproducible “de novo” browning differentiation model. Furthermore, the efficacy of the stimulation of the PPAR-γ pathway in obtaining a beige adipocyte phenotype demonstrates that RGZ can induce the browning process and elects it as a perfect reference compound for experimental procedures in this field.